Problem-based learning in communication systems using MATLAB and simulink - Choi, Kwonhue; Liu, Huaping (IEEE series on mobile & digital communication., 2016)
Designed to help teach and understand communication systems using a classroom-tested, active learning approach.- Resumé vydavatel